Supracondylar Displaced Fracture of Elbow in Children Treated with Closed Reduction and Percutaneous K Wire Fixation - Aqeel Moazzam, Agha Momin, Kamran Saeed, Naeem Mehmood Mughal, Muhammad Saleem Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the closed reduction and percutaneous K wire fixation method outcomes in the treatment of supracondylar displaced fracture of elbow in children. Study Design: Prospective study Place and Duration of Study: Department of Orthopaedics, Arif Memorial Teaching Hospital, Lahore from 2nd April 2021 to 31st September 2021. Methodology: One hundred and seventy children were included. Those children having supracondylar displaced fractures of elbow with a grade 3 were included in the study as participant. K wires of 1.5-2cm were used after closed reductions were satisfactorily achieved. Padded-Back slabs at posterior position of elbow were applied. At 2 weeks’ suture removal and pin configuration was also observed. Callus production was observed through radiological x ray images. Results: Majority of the children belonged to the age group of 6-10 years. There were 59.4% males while 40.58% were females. Within the total number of cases 55% were administered two lateral parallel K wires while 45% were administered cross K wire. Pin tract infection was formed in 2.5% of lateral K wire cases while it was observed in only 1.2 % of Cross wire cases. Most of the children got the fracture while playing a sport. The recovery phase was of 3.5 months while fracture joined in a mean value of 1 month. Conclusion: Lateral percutaneous pin technique for the management of supracondylar fracture of humerus bone is a more suitable method and offers same results without involvement of iatrogenic ulnar nerve injury. Keywords: Humerus, Ulnar nerve, Pin method, K-wire, Deformation